Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

A mutant (‘lab strain’) of the hyperthermophilic archaeon Pyrococcus furiosus, lacking flagella, has unusual growth physiology - Derrick L. Lewis; Jaspreet S. Notey; Sanjeev K. Chandrayan; Andrew J. Loder; Gina L. Lipscomb; Michael W. W. Adams; Robert M. Kelly (Extremophiles, 2015)

Larval lobster ( Homarus americanus ) distribution and drift in the vicinity of the Gulf of Maine offshore banks and their probable origins - G. C. HARDING; K. F. DRINKWATER; C. G. HANNAH; J. D. PRINGLE; J. PRENA; J. W. LODER; S. PEARRE; W. P. VASS (Fisheries Oceanography, 2005)
Surveys for lobster larvae in offshore waters of the north‐eastern Gulf of Maine in 1983, 1987 and 1989 confirm that local hatching occurs mainly at depths

Cod and haddock spawning on Georges Bank in relation to water residence times - F. H. Page; M. Sinclair; C. E. Naimie; J. W. Loder; R. J. Losier; P. L. Berrien; R. G. Lough (Fisheries Oceanography, 1999)
The seasonal and geographical patterns of spawning for Georges Bank cod ( Gadus morhua ) and haddock ( Melanogrammus aeglefinus ) are estimated using composite distributions of stage I eggs derived from the Marine Resources Monitoring, Assessment and Prediction (MARMAP) data set (1977–1987). The inferred mean spawning locations are compared with patterns in particle residence times derived from a three‐dimensional prognostic circulation model that estimates the tidal and seasonal mean circulation. The comparisons indicate that cod and haddock spawning occurs at times and locations characterized by model residence times in excess of 35 d. The results are discussed in the context of fish population regulation theory, particularly the member/vagrant hypothesis and the concept of abundance‐dependent vagrancy.